2021
DOI: 10.1038/s41467-021-22993-5
|View full text |Cite
|
Sign up to set email alerts
|

The histone variant H2A.W and linker histone H1 co-regulate heterochromatin accessibility and DNA methylation

Abstract: In flowering plants, heterochromatin is demarcated by the histone variant H2A.W, elevated levels of the linker histone H1, and specific epigenetic modifications, such as high levels of DNA methylation at both CG and non-CG sites. How H2A.W regulates heterochromatin organization and interacts with other heterochromatic features is unclear. Here, we create a h2a.w null mutant via CRISPR-Cas9, h2a.w-2, to analyze the in vivo function of H2A.W. We find that H2A.W antagonizes deposition of H1 at heterochromatin and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(127 citation statements)
references
References 56 publications
11
86
2
Order By: Relevance
“…We hypothesized that the expression patterns of H2A.W.6 and H2A.W.7 differ, leading to exposure of these two variants to contrasting activities that deposit and maintain KSPK phosphorylation. Contrary to our hypothesis, we observed that phosphorylation of KSPK in H2A.W.7 was still absent even when expressed under the control of the H2A.W.6 promoter in the triple mutant h2a.w-2 completely deprived of H2A.W [43] (Fig 4D). Furthermore, we observed phosphorylation of KSPK of the C-terminal tail of H2A.W.6 when fused to the core of H2A.W.7 irrespective of the promoter used (Fig 4D).…”
Section: Cross Talk Between Phosphorylation At the Kspk And Sq Motifs In H2a W7contrasting
confidence: 99%
See 4 more Smart Citations
“…We hypothesized that the expression patterns of H2A.W.6 and H2A.W.7 differ, leading to exposure of these two variants to contrasting activities that deposit and maintain KSPK phosphorylation. Contrary to our hypothesis, we observed that phosphorylation of KSPK in H2A.W.7 was still absent even when expressed under the control of the H2A.W.6 promoter in the triple mutant h2a.w-2 completely deprived of H2A.W [43] (Fig 4D). Furthermore, we observed phosphorylation of KSPK of the C-terminal tail of H2A.W.6 when fused to the core of H2A.W.7 irrespective of the promoter used (Fig 4D).…”
Section: Cross Talk Between Phosphorylation At the Kspk And Sq Motifs In H2a W7contrasting
confidence: 99%
“…Contrary to our hypothesis, we observed that phosphorylation of KSPK in H2A.W.7 was still absent even when expressed under the control of the H2A.W.6 promoter in the triple mutant h2a . w-2 completely deprived of H2A.W [ 43 ] ( Fig 4D ). Furthermore, we observed phosphorylation of KSPK of the C-terminal tail of H2A.W.6 when fused to the core of H2A.W.7 irrespective of the promoter used ( Fig 4D ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations